2013
DOI: 10.1007/978-3-642-40483-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Precise Pointing Techniques for Handheld Augmented Reality

Abstract: Abstract. We propose two techniques that improve accuracy of pointing at physical objects for handheld Augmented Reality (AR). In handheld AR, pointing accuracy is limited by both touch input and camera viewpoint instability due to hand jitter. The design of our techniques is based on the relationship between the touch input space and two visual reference frames for on-screen content, namely the screen and the physical object that one is pointing at. The first technique is based on Shift, a touch-based pointin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…al [6] was the first to propose the freeze-frame interaction paradigm as a method of annotation authoring. User studies conducted in later research confirmed that users perform better in such offline annotation authoring, when compared to online techniques [7,12].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…al [6] was the first to propose the freeze-frame interaction paradigm as a method of annotation authoring. User studies conducted in later research confirmed that users perform better in such offline annotation authoring, when compared to online techniques [7,12].…”
Section: Introductionmentioning
confidence: 77%
“…There is a clear benefit to such interaction, however such interaction introduces the need for precise hand tracking. Another alterative is to improve the stability of the cursor during the online interaction by attaching it to the physical object and using relative pointing as an input method [12]. Even though this improves the stability of interaction, the requirement to point the device at an object during annotation authoring is not optimal for such process.…”
Section: Introductionmentioning
confidence: 99%
“…Relative Pointing used in this experiment differs from the one described in [16]. In [16], we evaluated Relative Pointing as an interaction technique.…”
Section: Methodsmentioning
confidence: 99%
“…To improve the user interaction, they used both manual and automatic zooming as well as freeze-frame (i.e., pausing the live camera image). In [16], we proposed two pointing techniques for handheld AR: (1) combining Shift [17], a touchbased handheld device pointing technique, with freezeframe, and (2) extending the crosshair technique with a relative pointing mode where the cursor is stabilized on a physical wall map and controlled with finger strokes on the touch screen. The experiments indicated that those two techniques, Shift&Freeze and Relative Pointing, were preferred by users and were more accurate but longer to operate than both crosshair and direct touch.…”
Section: Handheld Ar Pointingmentioning
confidence: 99%
See 1 more Smart Citation